Effectiveness of a culturally appropriate intervention to prevent intimate partner violence and HIV transmission among men, women, and couples in rural Ethiopia: Findings from a cluster-randomized controlled trial - Sharma, Vandana; Leight, Jessica; Verani, Fabio; Tewolde, Samuel; Deyessa, Negussie (Public Library of Science, 2020)
Intimate partner violence (IPV) is associated with increased HIV risk and other adverse health and psychosocial outcomes. We assessed the impact of Unite for a Better Life (UBL), a gender-transformative, participatory intervention delivered to men, women, and couples in Ethiopia in the context of the coffee ceremony, a traditional community-based discussion forum. Villages (n = 64) in 4 Ethiopian districts were randomly allocated to control, men’s UBL, women’s UBL, or couples’ UBL, and approximately 106 households per village were randomly selected for inclusion in the trial. The intervention included 14 sessions delivered twice weekly by trained facilitators; control arm households were offered a short IPV educational session. Primary outcomes were women’s experience of past-year physical or sexual IPV 24 months postintervention. Secondary outcomes included male perpetration of past-year physical or sexual IPV, comprehensive HIV knowledge, and condom use at last intercourse. Additional prespecified outcomes included experience and perpetration of past-year physical and/or sexual IPV and emotional IPV, HIV/AIDs knowledge and behaviors, decision-making, and gender norms. An intention-to-treat (ITT) analysis was conducted, evaluating 6,770 households surveyed at baseline in 2014–2015 (1,680 households, 16 clusters in control; 1,692 households, 16 clusters in couples’ UBL; 1,707 households, 16 clusters in women’s UBL; 1,691 households, 16 clusters in men’s UBL). Follow-up data were available from 88% of baseline respondents and 87% of baseline spouses surveyed in 2017–2018. Results from both unadjusted and adjusted specifications are reported, the latter adjusting for age, education level, marriage length, polygamy, socioeconomic status, and months between intervention and endline. For primary outcomes, there was no effect of any UBL intervention compared to control on women’s past-year experience of physical (couples’ UBL arm adjusted odds ratio [AOR] = 1.00, 95% confidence interval [CI]: 0.77–1.30, p = 0.973; women’s UBL arm AOR = 1.11, 95% CI 0.87–1.42, p = 0.414; men’s UBL arm AOR = 1.02, 95% CI: 0.81–1.28, p = 0.865) or sexual IPV (couples’ UBL arm AOR = 0.86, 95% CI: 0.62–1.20, p = 0.378; women’s UBL arm AOR = 1.15, 95% CI: 0.89–1.50; p = 0.291; men’s UBL arm AOR = 0.80, 95% CI: 0.63–1.01, p = 0.062). For the secondary outcomes, only the men’s UBL intervention significantly reduced male perpetration of past-year sexual IPV (AOR: 0.73; 95% CI: 0.56–0.94, p = 0.014), and no intervention reduced perpetration of past-year physical IPV. Among women, the couples’ UBL intervention significantly improved comprehensive HIV knowledge, and both couples’ and women’s UBL significantly increased reported condom use at last intercourse. Among additional outcomes of interest, the men’s UBL intervention was associated with a significant reduction in women’s experience of past-year physical and/or sexual IPV (AOR = 0.81, 95% CI: 0.66–0.99, p = 0.036) and men’s perpetration of physical and/or sexual IPV (AOR = 0.78; 95% CI: 0.62–0.98, p = 0.037). UBL delivered to men and couples was associated with a significant reduction in HIV risk behaviors and more equitable intrahousehold decision-making and household task-sharing. The primary limitation is reliance on self-reported data. A gender-transformative intervention delivered to men was effective in reducing self-reported perpetration of sexual IPV but did not reduce IPV when delivered to couples or women. We found evidence of decreased sexual IPV with men’s UBL across men’s and women’s reports and of increased HIV knowledge and condom use at last intercourse among women. The men’s UBL intervention could help accelerate progress towards gender equality and combating HIV/AIDS.